Customers' Behavior to Using the M-money Application of Lao Telecom Communication in Luang Prabang - bounnaponh, chandala (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aimed to study the app usage behavior of customers of the Lao Telecom State Enterprise, Luang Prabang Branch, specifically focusing on the use of the M-Money application. A quantitative research method was employed, utilizing both descriptive and statistical analysis. Data were collected from relevant documents, related dissertations, and online sources. Additionally, 300 questionnaires were distributed to users of the M-Money wallet app in Luang Prabang Capital. The collected data were analyzed using the SPSS statistical software. The findings revealed the following usage behaviors: The majority of users (96 people or 32.0%) became aware of the M-Money app through the Internet. Most respondents (102 people or 34.0%) had been using the app for 3–4 months. The primary purpose for using the app was mobile phone top-ups (140 people or 46.7%), while the most common method for transferring money was through the BCEL One banking app (155 people or 51.7%). Regarding spending habits, 144 users (48.0%) typically spent between 50,000–100,000 kip per transaction. In terms of frequency, 95 respondents (31.7%) used the app 5–6 times per day. The most common use case was topping up or purchasing packages (217 people or 72.3%), with the peak usage time between 18:01 and 24:00 (115 people or 38.3%). A significant portion of users (167 people or 55.7%) appreciated the convenience of not needing to carry cash. All respondents (100%) accessed the app via mobile devices.